IL-17 Producing Lymphocytes Cause Dry Eye and Corneal Disease With Aging in RXRα Mutant Mouse - Alam, Jehan; Yazdanpanah, Ghasem; Ratnapriya, Rinki; Borcherding, Nicholas; de Paiva, Cintia S.; Li, DeQuan; Guimaraes de Souza, Rodrigo; Yu, Zhiyuan; Pflugfelder, Stephen C. (Frontiers in Medicine, 2022)
Purpose To investigate IL-17 related mechanisms for developing dry eye disease in the Pinkie mouse strain with a loss of function RXRα mutation. Methods Measures of dry eye disease were assessed in the cornea and conjunctiva. Expression profiling was performed by single-cell RNA sequencing (scRNA-seq) to compare gene expression in conjunctival immune cells. Conjunctival immune cells were immunophenotyped by flow cytometry and confocal microscopy. The activity of RXRα ligand 9-cis retinoic acid (RA) was evaluated in cultured monocytes and γδ T cells. Results Compared to wild type (WT) C57BL/6, Pinkie has increased signs of dry eye disease, including decreased tear volume, corneal barrier disruption, corneal/conjunctival cornification and goblet cell loss, and corneal vascularization, opacification, and ulceration with aging. ScRNA-seq of conjunctival immune cells identified γδ T cells as the predominant IL-17 expressing population in both strains and there is a 4-fold increased percentage of γδ T cells in Pinkie. Compared to WT, IL-17a, and IL-17f significantly increased in Pinkie with conventional T cells and γδ T cells as the major producers. Flow cytometry revealed an increased number of IL-17+ γδ T cells in Pinkie. Tear concentration of the IL-17 inducer IL-23 is significantly higher in Pinkie. 9-cis RA treatment suppresses stimulated IL-17 production by γδ T and stimulatory activity of monocyte supernatant on γδ T cell IL-17 production. Compared to WT bone marrow chimeras, Pinkie chimeras have increased IL-17+ γδ T cells in the conjunctiva after desiccating stress and anti-IL-17 treatment suppresses dry eye induced corneal MMP-9 production/activity and conjunctival goblet cell loss. Conclusion These findings indicate that RXRα suppresses generation of dry eye disease-inducing IL-17 producing lymphocytes s in the conjunctiva and identifies RXRα as a potential therapeutic target in dry eye.